Assessment of Organizational Commitment and Psychosocial Risk Factors: Empirical evidence from micro-enterprises in Ecuador - Guamán-Guevara, María Dolores; Ipanaqué-Costilla, Joward; Guamán- Guevara, Fabricio (Revista Venezolana de Gerencia, 2025)
The present research aims to establish the underlying factors influencing the current organizational commitment levels presented by salespersons of trading companies in the footwear sector in the Tungurahua Province-Ecuador. Between January and July 2024, 237 salespersons completed a semi-structured questionnaire regarding sociodemographic and company-related variables, psychosocial risk factors, and the traditional organizational commitment model components (affective, normative, and continuum). The collected data were quantitatively analyzed using Spearman’s correlation and multiple linear regression model. Findings showed a moderate negative relationship between psychosocial risk factors and organizational commitment levels (r =-0.558). Furthermore, the three organizational commitment components and external factors positively influenced organizational commitment. In contrast, leadership, recovery and company location negatively influenced organizational commitment. These findings underscore the critical role of organizational and environmental conditions in shaping employees’ engagement, reinforcing prior research that emphasizes the deleterious effects of workplace stressors.